Systemic Lupus Erythematosus Presenting With Thrombotic Thrombocytopenic Purpura at Onset: A Case Report - Takagi, Yoko; Kobayashi, Yasuko; Hirakata, Ayako; Takei, Mariko; Ogasawara, Satoshi; Yajima, Chikage; Ikeuchi, Yuka; Matsumoto, Akira; Ogawa, Yoshiyuki; Handa, Hiroshi; Matsumoto, Masanori; Arakawa, Hirokazu; et al. (Frontiers in Pediatrics, 2022)
Background: Thrombotic microangiopathy (TMA) is a syndrome associated with hemolytic anemia, thrombocytopenia, and various organ disorders. Thrombotic thrombocytopenic purpura (TTP) is a disease that develops when a disintegrin-like and metalloproteinase with thrombospondin type l motif 13 (ADAMTS13) activity decreases to <10% of that in normal plasma, causing platelet thrombocytosis in microvessels throughout the body. Currently, ADAMTS13-deficient TMA is diagnosed as TTP. Systemic lupus erythematosus (SLE)-related TMA includes both acquired TTP, in which ADAMTS13 activity is significantly reduced, and secondary TMA, in which ADAMTS13 activity is not reduced. Both diseases have different prognoses. Case presentation: An 11-year-old girl was admitted to our hospital on suspicion of TMA with thrombocytopenia and hemolytic anemia. Because the patient had hypocomplementemia, SLE-related TMA or complement-related TMA were considered. Therefore, we initiated plasma exchange (PE) for the patient. Subsequently, she fulfilled the pediatric SLE diagnostic criteria, and ADAMTS13 activity was shown to be decreased and anti-ADAMTS13 antibody titer increased. She was thus diagnosed with secondary TTP caused by SLE. Treatment response was good as platelet count and ADAMTS13 activity improved with three times of PE, followed by methylprednisolone pulse therapy and administration of mycophenolate mofetil. Renal pathology showed thrombus formation in glomerular arterioles and lupus nephritis categorized as class III (A) of the International Society of Nephrology and the Renal Pathology Society classification. Because the patient was thought to be in the high-risk group of SLE, three courses of intravenous cyclophosphamide pulse therapy were administered as an additional induction therapy. No recurrence of TTP was observed. Conclusion: In SLE-related TMA, measurement of ADAMTS13 activity and anti-ADAMTS13 antibody titer are necessary for diagnosis, and for predicting prognosis and recurrence of the disease; however, in the acute phase of immune-mediated TMA, it is important to initiate proper treatments even before knowing the results to improve prognosis.